MODEL STRUKTURAL HUBUNGAN BUDAYA ORGANISASI, KOMPETENSI PENGGUNA, PENGENDALIAN INTERNAL DAN KUALITAS INFORMASI AKUNTANSI PEMERINTAH DAERAH - Rima Rachmawati (MIX: Jurnal Ilmiah Manajemen, 2018)
Abstract. This study aims to prove the influence of organizational culture, user competence and internal control to the quality of Regional Financial Management Information Sistem (abbreviation=SIPKD), and to also prove the quality of SIPKD relationship to the quality of accounting information. Survey in Garut local government as many as 75 of SIPKD users. Data analysis using Structural Equation Modeling (SEM) with Partial Least Square approach (PLS). The SEM PLS consists of two evaluation; inner model and structural model. The result of the research indicate that there is an effect of internal control on the creation of quality SIPKD, and quality SIPKD can influence the creation of quality accounting information. While the organization culture and user competence is not proven to influence the creation of quality SIPKD. Research implications can solve the problem of accounting information sistems, especially in the local government of Garut.